Sufficiency Criteria for a Class of -Valent Analytic Functions of Complex Order - Muhammad Arif (Abstract and Applied Analysis)
In the present paper, we consider a subclass of -valent analytic functions and obtain certain simple sufficiency criteria by using three different methods for the functions belonging to this class. Many known results appear as special consequences of our work.